Dual Stage Trade Credit Policy for Integrated Inventory System - DEM, HIMANI; CHAUDHARY, ARUN (The journal of contemporary issues in business and government, 2021)
The present study considers an integrated production inventory system of a supplier and a retailer. The proposed model explores the vendor managed strategy with the dual stage trade credit also known as progressive payment scheme, lead time and shortages. A nonlinear problem is formulated for the purpose of total profit maximization and solved using conventional global optimization method for nonlinear problem. This article can provide the managerial outline for schematizing the production strategy according to the received orders in a joint business enterprise.